Exploring the impact of Islamic prayer (‘salat’) on tear film parameters: An observational study - Meznah Saud Almutairi; Alshaibani, Azizah; Altoaimi, Basal Hamad; El-Hiti, Gamal Abdel-Rahman (Journal of the Pakistan Medical Association, 2026)
Objective: To explore the impact of ‘salat’ on the comfort, stability, and quality of tear film. Method: The observational, comparative study was conducted in June 2024 at the College of Applied Medical Sciences in Riyadh, Saudi Arabia, and included subjects aged 18-40 years who were randomly recruited. The subjects were asked to wash (‘wudu’) in preparation for ‘salat’. The measurements were carried out before ‘salat’, and again once they had performed ‘salat’ (four ‘rakat’). The standard patient evaluation of eye dryness questionnaire was used to assess patient comfort first. The non-invasive tear breakup time and tear ferning tests were then used to assess the stability and quality of the tear film, respectively. The tests were performed on the subjects’ right eyes with a 5-minute gap. Data was analysed using SPSS 22. Results: Of the 100 subjects with a mean age of 22.3±4.5 years, 62(62%) were females and 38(38%) were males. Significant differences were found in the median scores related to eye dryness, tear breakup time, and tear ferning before and after ‘salat’ (p<0.05). Conclusions: Islamic prayer (‘salat’) was found to have a positive effect on tear film parameters. Keywords: Dry eye syndromes, Eye abnormalities, Tears, Faith-healing, Religion.